LEGISLASI ANAK BIOLOGIS: (Studi Deskriptif Analitik melalui Kajian Hadits Tematik) - Syahriyati, Laili ‘Izza (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2020)
Natural child only have a nasab from his mother. Constitutional Court No.46/PUU- VIII/2010 add a child outside of marriage also connected to the biological father in civil. This provision aims to provide fair legal protection and certainty about child born. But, Indonesian Religious Leader (MUI) provide fatwa No 11/2012 about the position of the natural child and the treatment of it. This research will discuss about Hadith study is related to biological child legislation and legal content in it. The type of research is yuridis-normative. This research analizes law phenomena with nash, hadits and opinion of fiqh scholars about that. The Research result is HR.Abu Daud- 2266, HR.Bukhari ke-6319, HR.Bukhari- 4903 talk about natural child has nasab to the mother only. Next, HR.Bukhari ke-1271 about a child is always born with fitrah and can’t accept guilt of his parents. Jumhur scholars besides Hanafiyyah agreed about natural child has nasab with mother’s. But, Hanafiyyah is explain natural child have conecting nasab with biological father because his father and profeble.